1987
DOI: 10.1029/wr023i007p01162
|View full text |Cite
|
Sign up to set email alerts
|

Optimal groundwater quality management under parameter uncertainty

Abstract: To date optimization models for groundwater quality management give no assurance that water quality standards will be met. This is in part because they ignore errors in hydraulic heads, flows, and solute concentrations due to flow and transport model parameter uncertainty. Here we explicitly incorporate parameter estimation and estimate uncertainties into a model for the optimal design of an aquifer remediation scheme. Parameter uncertainty is incorporated into the decision‐making process. The objective is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
139
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 263 publications
(141 citation statements)
references
References 29 publications
0
139
0
2
Order By: Relevance
“…Examples of stochastic simulation-optimization formulations for cases primarily involving aquifer remediation are the studies reported by Tung [1986], Wagner and Gorelick [1987], Gaily and Gorelick [1993], and Tiedeman and Gorelick [1993]. Stochastic optimization that includes a comprehensive sensitivity analysis has yet to be applied to groundwater resource allocation in hydroecologically sensitive regions.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of stochastic simulation-optimization formulations for cases primarily involving aquifer remediation are the studies reported by Tung [1986], Wagner and Gorelick [1987], Gaily and Gorelick [1993], and Tiedeman and Gorelick [1993]. Stochastic optimization that includes a comprehensive sensitivity analysis has yet to be applied to groundwater resource allocation in hydroecologically sensitive regions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most difficult issues in groundwater management modeling is dealing adequately with the effect of model uncertainty in optimal decision making (Wagner and Gorelick, 1987). The uncertainty stems from a wide variety of factors ranging from partial knowledge about the aquifer properties, its boundary conditions, land use practices, onground nitrogen loading, nitrogen soil dynamics, soil characteristics, depth to water table, flow and transport parameters affecting nitrate fate and transport in groundwater, to economic, regulatory and political factors.…”
Section: Stochastic Modeling Frameworkmentioning
confidence: 99%
“…Unlike the classic chance-constrained applications (e.g., Tung, 1986;Wagner and Gorelick 1987;McSweeny and Shortle, 1990;Wagner 1999), this formulation considers uncertainty in the response matrix coefficients and does not require a priori definition of the distribution. The "classic" chance-constrained programming (Charnes et al, 1958;Charnes and Cooper, 1963) is a stochastic programming method that enables the integration of parameter uncertainties into the optimization framework at time that permits constraint violations up to specified probability limits.…”
Section: Mixedinteger Stochastic Optimization Model Withmentioning
confidence: 99%
See 2 more Smart Citations